Design and fabrication of haptic touch sensor for soft robotic applications - Syazlin Mohd Azli (Nanyang Technological University, 2022)
Like humans, the sense of touch is essential for a soft robot to grasp and understand their surroundings. Hence, touch sensing or tactile perception is incredibly significant for a soft robot to feel and touch an object and/or the environment. The amount of pressure needed to identify an object differs on the haptic sensor properties such as, the type of materials, the patterned shape, the conductivity layers used, as well as the hardness. Therefore, it is imperative to do an experiment on a variety of pressure sensors, with several types of materials, and/or shape and/or conductivity layers to develop an optimized pressure sensor with wide sensing range, high sensitivity, and good mechanical durability for practical applications. Thus, the objective of this project is to design and fabricate soft haptic touch sensors.